Pengaruh Teknologi Informasi, Pengendalian Internal dan Kompetensi Pengguna Terhadap Kualitas Sistem Informasi Akuntansi - Ninda Sherly Anggraini; Cris Kuntadi; Rachmat Pramukty (Manajemen Kreatif Jurnal, 2023)
In a research or scientific publication, previous research is very important. Theories and phenomena of the relationship or influence between variables are strengthened by previous research or ongoing research. Analysis of the Accounting Information Systems literature is used to analyze aspects that affect the Quality of Accounting Information Systems, particularly Information Technology, Internal Control, and User Competence. The purpose of this article is to develop hypotheses about how different variables interact that can be applied to future research. Scientific work is written using a qualitative approach and library research. Examine the theory and the relationship or influence between variables in books and journals that you find online or offline in the library using Mendeley, Scholar, Google, and other sources. The findings of this literature review are as follows: Information Technology influences the quality of accounting information systems; Internal Control affects the quality of accounting information systems; and User Competence affects the quality of accounting information systems.